Criptografia RSA e a Teoria dos Números - Lima, Roberval da Costa (2013)
In this work we present the concept of cryptography, highlighting the differences between symmetric encryption and asymmetric encryption. We also show how RSA encryption works. Moreover, we study the main mathematical results that justify the operation of this cryptosystem and its security, such as: congruences, Euler's theorem, Fermat's Little Theorem, Wilson's Theorem, Euler's criterion for quadratic residues, Law of Quadratic Reciprocity and primality tests.